James Joyce and cinematicity : before and after film - Williams, Keith, 1958- (Edinburgh University Press, 2020)
"In this book, Keith Williams explores Victorian culture's emergent 'cinematicity' as a key creative driver of Joyce's experimental fiction, showing how Joyce's style and themes share the cinematograph's roots in Victorian optical entertainment and science. The book reveals Joyce's references to optical toys, shadowgraphs, magic lanterns, panoramas, photographic analysis and film peepshows. Close analyses of his works show how his techniques elaborated and critiqued their effects on modernity's 'media-cultural imaginary'."--